(untitled) (ENTHYMEMA, 2019)
In a famous metaphor, Freud compares psychoanalysis to sculpture rather than to painting because, while the latter adds something in order to depict, the sculpture takes away something to achieve the same result. It is on the same line as Michelangelo, who had said that the block of marble on which he worked, already contained the statue he had in mind: it was only a matter of removing the more preventing his vision. What the patient in treatment shows, is intended to be similar to the excess of marble in sculpture; it covers the most important thing even if this one is hidden. Lacan takes this concept to the extreme by affirming that the essence of psychoanalytic theory is a speech without words. Poetry too, this thesis is expressed here, is the form of art which finds expression per via di levare, because its essence is not sayable: as some poets show, including Quasimodo and Verlaine, the task of poetry is to subtract this not sayable from nothing. Otherwise it is only elocutio, the art of saying in a good manner.